Rozwiąż równania a) - 3 ∙ x = 2 ∙ x + 10 b) 8 ∙ x – 6 =3 ∙ x +14



Odpowiedź :

Odpowiedź:

a)   -3*x = 2 *x +10

      -3x = 2x+10

-3x - 2x= 10  /*(-1)

       3x+2x= - 10

       5x= - 10/:5

             x= - 2

spr..  -3 *(-2 )= 2*(-2)+10

               6= -4+10

                6=6

                 L=P

b)  8*x -6= 3*x +14

       8x-6= 3x+14

          8x-3x= 14 +6

                5x= 20 /:5

            x= 4

spr..  8*4 -6= 3*4+14

                 32-6= 12+14

                26=26

                   L=P

Szczegółowe wyjaśnienie:

Odpowiedź:

a) -3*x=2*x+10

-3x= 2x+10

-3x-2x=10

-5x=10 /:-5

x=-2

b) 8*x-6=3*x+14

8x-6=3x+14

8x-3x=14+6

5x=20 /:5

x=4

Szczegółowe wyjaśnienie: